2004
DOI: 10.1007/s11176-005-0121-5
|View full text |Cite
|
Sign up to set email alerts
|

Complex formation of pyridine N-oxides with iodine

Abstract: Complex formation of N-oxides of pyridine, 2-and 3-picolines, 4-nitropyridine, and 2,6-lutidine with iodine in benzene solutions and binary solid mixtures gives rise to equimolar complexes. In the solid phase, 1 : 2 and 2 : 1 complexes are also formed. Most solid complexes are polymorphous, and the enthalpies of intermolecular bonds in different crystal modifications are different. In solutions, [external] complexes pass into more stable [internal] complexes. The formation enthalpies of external and internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The ability of heteroaromatic N- oxides and diiodine to form strong halogen bonds and the possibility of the use of such bonding in catalysis raise the interest to the structural and electronic features of the complexes comprising these two molecules. The authors of the earlier studies suggested several possible modes of their interactions, such as σ-bonding of diiodine with oxygen or π-bonding with a parallel arrangement of the diiodine molecule above the aromatic ring of N- oxide. These suggestions, however, were based on the results of NMR, IR, and/or UV–vis measurements. Despite the fact that the discussion of the complexes of diiodine with N- oxides has continued for more than 50 years, ,,, the definitive elucidation of their structures via X-ray structural analysis is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of heteroaromatic N- oxides and diiodine to form strong halogen bonds and the possibility of the use of such bonding in catalysis raise the interest to the structural and electronic features of the complexes comprising these two molecules. The authors of the earlier studies suggested several possible modes of their interactions, such as σ-bonding of diiodine with oxygen or π-bonding with a parallel arrangement of the diiodine molecule above the aromatic ring of N- oxide. These suggestions, however, were based on the results of NMR, IR, and/or UV–vis measurements. Despite the fact that the discussion of the complexes of diiodine with N- oxides has continued for more than 50 years, ,,, the definitive elucidation of their structures via X-ray structural analysis is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The congregated electron phase model was firstly proposed by Ponomarenko [19] to calculate the slag composition activity and also tested and confirmed by authors in the vanadium and titanium distribution system between metal and slag. [20,21] In CEPM, the components concentrations were expressed by the atom mole fraction and the activity of constituents in slag system were evaluated by the phase electronic partial molar Gibbs free energy (Fermi level), which consulted the form of regular solution (a BO = c B AE x B ) to investigate the activity.…”
Section: A Reaction Mechanism Of Desulfurization and Resulfurizationmentioning
confidence: 99%
“…The derivation processes applied to study the sulfur activity in slag according to CEPM are described in Eqs. [19] through [22].…”
Section: A Reaction Mechanism Of Desulfurization and Resulfurizationmentioning
confidence: 99%
See 1 more Smart Citation